PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE DAN DISIPLIN KERJA TERHADAP KUALITAS LAPORAN KEUANGAN: STUDI EMPIRIS PADA BANK PERKREDITAN RAKYAT DI KABUPATEN PATI - Adi Andrian; Ashari Ashari; Dennyca Hendriyanto N (Gapenas Publisher, 2022)
This study aims to analyze the effect of human resource competence, utilization of information technology, application of the principles of good corporate governance and work discipline on the quality of financial reports (empirical study on rural banks in Pati district). The sampling technique used was purposive sampling technique with the number of respondents obtained as many as 90 respondents. Partially, the competence of human resources affects the quality of financial reports. Meanwhile, the use of information technology, the application of the principles of good corporate governance and work discipline have no effect on the quality of financial reports.